Gas Kinetics, Rumen Characteristics, and In Vitro Degradability of Varied Levels of Dried and Fresh Cassava Leaf Top Fermented with Cassava Pulp - Morm, S.; Lunpha, A.; Pilajun, R.; Cherdthong, A. (Tropical Animal Science Journal, 2023)
The purpose of this study was to determine the impact of different levels of dried cassava leaf top (DCT) and fresh cassava leaf top (FCT) fermented with cassava pulp (CS) on the nutritional value of silage, gas kinetics, rumen characteristics, and in vitro degradability. Dietary treatments were administered using a completely randomized design (CRD) with eight treatments and three replicate runs. The eight treatments were as follows: 1) CS fermented no additive (nA), 2) CS fermented with additives (Saccharomyces cerevisiae, urea, molasses, and sugar) (CSA), 3) 95% CSA fermented with 5% DCT (5DCT), 4) 90% CSA fermented with 10% DCT (10DCT), 5) 85% CSA fermented with 15% DCT (15DCT), 6) 95% CSA fermented with 5% FCT (5FCT), 7) 90% CSA fermented with 10% FCT (10FCT), 8) 85% CSA fermented with 15% FCT (15FCT), respectively. After 21 days of fermentation, samples of the silages were taken for chemical analysis and utilized to examine the in vitro gas production and degradability. The results show that fermented CS with DCT at 5% to 10% DM had the highest increase in CP when compared to nA or CSA (p